(untitled) (Jurnal Manajemen dan Organisasi, 2016)
The competition is very tight, so M-BRIO Food Laboratory as one of the food testing laboratory requires suitable of marketing strategy. The purpose of this study were (1) Identify and analyze internal and external environmental factors that affect effectivity of the marketing strategy at M-BRIO Food Laboratory, (2) Recommend priorities and appropriate marketing strategies can be applied to the M-BRIO Food Laboratory. Formulation of marketing strategies that go through three stages, (1) the input stage using EFE matrix and IFE matrix,(2) matching stage using the SWOT matrix and,(3) decision stages using paired comparison method for selecting alternative strategies and continued with the analitycal hierarchy process (AHP) method to prioritize marketing strategies appropriate for the company. Internal environmental factors that become the main force is lead by a food expert that has been recognized nationally and internationally. While its main weakness are display of exterior and interior of the laboratory building has not been well-organized and performance of employees who have not been standardized. External environmental factors that can be used as the main opportunity is the development of the technology food testing laboratory. While the main threat for companies is bargaining power of consumers against the company’s so high. Priorities recommended marketing strategies are (1) Conduct promotion and education to inform the quality of service, scope of product coverage and the parameters that have been accredited, to food companies, (2) campaign of food safety to the public as a form of promotion and education through food expert as endorser.